Physiological attributes of jatropha under different planting densities and nitrogen doses - Allan R. F. Campos; Rosiane L. S. de Lima; Carlos A. V. de Azevedo; Ronaldo do Nascimento; Sonivagno S. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Nitrogen (N) fertilization associated with planting density is a practice that can improve the physiological aspects and consequently increase the yield of a crop. Thus, this study aimed to evaluate the effects of planting density and N levels on the physiological aspects of jatropha in the ‘Agreste’ region of Paraíba. Treatments consisted of four planting densities (833, 1,111, 1,666 and 2,500 plants ha-1) representing the plots and five N doses (0, 40, 80, 120 and 180 kg ha-1) corresponding the subplots. The effects of treatments on CO2 assimilation rate, internal CO2 concentration, transpiration, stomatal conductance, water use efficiency, instantaneous carboxylation efficiency and SPAD index were analysed. Except for stomatal conductance, the other variables were influenced by the interaction between planting densities and N levels. The association of the dose of 80 kg ha-1 with a planting density of 2,200 plants ha-1 provided adequate conditions for the production of plants with increased photosynthetic activity and efficient use of water.